Institutional Improvement in Supporting the Carrying Capacity of The Kendari City Coastal Area, Indonesia - Munawir, Abdillah; Rusdiyanto, Edi; Soesanta, Prabawa Eka; Muna, Siti Umamah Naili (ASTONJADRO, 2023)
This research is an escalating the environmental management of Kendari Bay coastal areas using an interpretatively structural modeling (ISM) technique. The fundamental circumstances of various problems in the coastal areas of Kendari Bay become complex due to the involvement of many interested parties (stakeholders) such as local government, communities, industries, merchants, hotel's owners, and non-governmental organizations (NGOs), and dynamic because the degradation rate of the coastal environment will change over time. This research aimed to seek the institutional roles in terms of concerned institutions, related government policies, and the needed programs in managing the coastal areas of Kendari Bay. Data collection was conducted from August to October 2018. Data were gathered through interviews, observation, and focus group discussions by using a technique of Interpretatively Structural Modelling (ISM). Results of this research exhibit that key elements of prioritized programs were information system development, research and development consolidation, clean the Kendari Bay movement and against pollution socialization, the establishment of community or custom-based organizations, and creating a coastal development agent of the bay. Furthermore, the results of analyzing the institutional key elements in broadening environmental management of Kendari Bay coastal areas were suggested to increase multi-sectors coordination among institutions such as Marine and Fishery Office, Regional Development Agency (Bappeda), Settlements and Public Housing Office, Environmental Office, Traditional Leaders, Watershed Management Agency, and Forestry Office. Those institutions in the analysis were hoped to be standard institutions in expanding the management of Kendari Bay coastal areas sustainably.